2019
DOI: 10.3390/polym11020345
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Discharge Characteristics of Textile Energy Storage Devices Having Different PEDOT:PSS Ratios and Conductive Yarns Configuration

Abstract: Conductive polymer PEDOT:PSS, sandwiched between two conductive yarns, has been proven to have capacitive behavior in our textile energy storage devices. Full understanding of its underlying mechanism is still intriguing. The effect of the PEDOT to PSS ratio and the configuration of the electrode yarns are the focus of this study. Three commercial PEDOT:PSS yarns, Clevios P-VP-AI-4083, Ossila AI 4083, and Orgacon ICP 1050, as well as stainless steel and silver-coated polybenzoxazole (Ag/PBO) yarns, in various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Textile based supercapacitors have attracted attention due to their inherent flexibility and their potential use in wearable electronics. Nuramdhani et al demonstrated that PEDOT:PSS sandwiched between two stainless steel conductive yarns showed capacitive behavior as an energy storage device [26]. Ma et al reported flexible stainless steel/cotton blend yarn coated with PEDOT:PSS and PPy which can be cycles up to 5000 cycles [102].…”
Section: Energy Harvesting and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Textile based supercapacitors have attracted attention due to their inherent flexibility and their potential use in wearable electronics. Nuramdhani et al demonstrated that PEDOT:PSS sandwiched between two stainless steel conductive yarns showed capacitive behavior as an energy storage device [26]. Ma et al reported flexible stainless steel/cotton blend yarn coated with PEDOT:PSS and PPy which can be cycles up to 5000 cycles [102].…”
Section: Energy Harvesting and Storagementioning
confidence: 99%
“…The focus will therefore be on enhancing durability, textile character, and conductivity. The use of electrically conductive polymeric materials have recently attracted considerable interest from academic and industrial researchers to explore their potential in sensors [22], biomedical [23], wireless communication patch antenna [24], energy harvesting [25] and energy storage [26] applications. Conductive polymers are light weight and flexible and can be applied on the textile without affecting its flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding electrical and optical properties presented by these materials makes them excellent candidates for a large number of applications in the field of electronics. Conducting polymers have been extensively studied as part of energy storage systems [2,3,4], solar cells [5,6,7], electromagnetic interference shielding [8,9,10], or light-emitting diodes [11,12,13] among others. All these new systems within the framework of conventional electronics have allowed the appearance of new electronic devices such as smart windows, new display devices, or long-lasting batteries [14].…”
Section: Introductionmentioning
confidence: 99%
“…3. Nuramdhani et al also used an Arduino Uno as a not-integrated part to investigate a textile energy storage device [34], while Li et al applied an Arduino ATmega2560 for data collection and visualization of a step pressure sensing and position mapping system, based on textile pressure sensor mats [35]. Frequency-based measurements in smart textiles were also applied by an Arduino Uno placed next to the textile fabric under investigation [36].…”
Section: Recent Sbcs and Sbmsmentioning
confidence: 99%